Peran Empowering Leadership Terhadap Efektivitas Kelompok Kerja Dalam Situasi Working From Home - Hanifah Nur Arini; Mulyani, Siti (UNIB Press, 2022)
The COVID-19 pandemic situation which began to endemic in 2020 in Indonesia changed various lines of life. The work system is no exception, which forms new work behaviors such as working from home. Managing work teams to remain effective in working from home conditions is a challenge for managers. The purpose of this study is to get an overview of the role of empowering leadership on the effectiveness of working groups in working from home situations by examining a number of literatures. The results of the study show that working from home has a positive or negative influence on the effectiveness of the work group. The positive effects of working from home include having their own work schedule autonomy, while the negative impacts are a decrease in work motivation, not achieving work-life balance and decreasing team performance productivity (difficulty in supervising work, completing work that takes longer and difficulties in coordinating). Leadership with empowering characteristics is able to promote a harmonious relationship pattern between leaders and subordinates to foster the empowerment of their subordinates' abilities to lead themselves and be responsible for their own actions. The characteristics of empowering leaders are able to help employees increase motivation and encourage the creation of effective team performance in working from home situations.